Management of Inflammation in Chronic Obstructive Pulmonary Disease-Update - Barman, Rakhal Chandra; Alam, Md Towhid; Islam, MM Shahin Ul; Ahmed, Sk Abdul Momen; Biswas, Gonopati; Howlader, Md Anwar Anwar Rahman; Fattah, Sk Abdul (Faridpur Medical College Journal, 2013)
Chronic obstructive pulmonary disease (COPD) is a systemic inflammatory condition, the earliest manifestation of which is airway obstruction which is only partially reversible and the treatment rationales are provided accordingly. Research has shown that COPD-inflammation involves multiple inflammatory cells and mediators and the underlying pathology differs from asthma inflammation.For these reasons, therapeutic agents that are effective in asthma patients may not be optimal in COPD patients. COPD exacerbations are intensified inflammatory events compared with stable COPD. The clinical and systemic consequences believed to result from the chronic inflammation observed in COPD, suggest that inflammation intensity is a key factor in COPD and exacerbation severity and frequency. Although inhaled corticosteroids are commonly used and are essential in asthma management, their efficacy in COPD is limited, with only a modest effect at reducing exacerbations. The importance of inflammation in COPD needs to be better understood by clinicians, and the differences in inflammation in COPD versus asthma should be considered carefully to optimize the use of anti-inflammatory agents. Current COPD management focuses predominantly on symptom relief by optimizing bronchodilatation. The role of phosphodiesterase type 4 inhibitors (PDE4), statins, angiotensin converting enzyme inhibitors, theophylline and tumor necrosis factor inhibitors in COPD management will be reviewed. Targeting COPD inflammation with the goal of reducing exacerbations is a major focus of current clinical practice & outcome research. DOI: http://dx.doi.org/10.3329/fmcj.v8i1.16897 Faridpur Med. Coll. J. 2013;8(1): 34-39